Catalytic growth of vertically aligned neutron sensitive 10Boron nitride nanotubes - Ahmad, P.; Khandaker, Mayeen Uddin; Amin, Yusoff Mohd; Khan, G.; Ramay, S.M.; Mahmood, A.; Amin, M.; Muhammad, N. (Springer Verlag, 2016)
10Boron nitride nanotubes (10BNNTs) are a potential neutron sensing element in a solid-state neutron detector. The aligned 10BNNT can be used for its potential application without any further purification. Argon-supported thermal CVD is used to achieve vertically aligned 10BNNT with the help of nucleation sites produced in a thin layer of magnesium–iron alloy deposited at the top of Si substrate. FESEM shows vertically aligned 10BNNTs with ball-like catalytic tips at top. EDX reveals magnesium (Mg) contents in the tips that refer to catalytic growth of 10BNNT. HR-TEM shows tubular morphology of the synthesized 10BNNT with lattice fringes on its outer part having an interlayer spacing of ~0.34 nm. XPS shows B 1 s and N 1 s peaks at 190.5 and 398 eV that correspond to hexagonal 10Boron nitride (10h-BN) nature of the synthesized 10BNNT, whereas the Mg kll auger peaks at ~301 and ~311 eV represents Mg contents in the sample. Raman spectrum has a peak at 1390 (cm−1) that corresponds to E2g mode of vibration in 10h-BN.